Analisis Kesalahan Penulisan Kutipan Pada Makalah Mahasiswi PGSD Universitas Negeri Medan - Rahel Valencia Tampubolon; Nurfadhilah Nasution; Deepa Yanti; Indah Aqilah Putri Lubis; Juwita Inggrid Sinaga; Wisman Hadi (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research aims to analyze errors in writing quotations in students' papers from the PGSD Study Program at Medan State University, especially in the paper entitled "Analysis of Teacher Difficulties in Implementing the Problem Based Learning Model in Elementary School Social Sciences Learning". This research uses a qualitative method with a design that prioritizes data collection through document analysis. The main data source comes from the text of the researched papers, with a focus on formatting errors, sources, and citation integrity. The data analysis technique uses the Miles and Huberman model which includes presenting data and drawing conclusions. The research results showed that there were inconsistencies in writing the author's name, the wrong writing order based on the year of publication, and the use of inappropriate punctuation in quotations. These findings emphasize the importance of understanding and applying correct citation writing rules to improve the quality of scientific literature.